Angiospermic flora of Runctia sal forest, Bangladesh. II. Magnoliopsida (Dicots) (Bangladesh Journal of Plant Taxonomy, 2010)
This paper deals with a total of 153 plant species under 120 genera and 52 families of the division Magnoliopsida (Dicots) of the Runctia Sal forest in Sherpur district. Habit analysis shows that herbs are represented by 34, shrubs 36, trees 65, climbers 17 and epiphyte by a single species. Updated nomenclature, habit, habitat and representative specimen have been furnished under each taxon.Keywords: Angiosperms; Magnoliopsida; Runctia sal forest.DOI: 10.3329/bjpt.v17i1.5389Bangladesh J. Plant Taxon. 17(1): 33-53, 2010 (June)